1994
DOI: 10.1111/j.1399-0004.1994.tb04216.x
|View full text |Cite
|
Sign up to set email alerts
|

Heredity in dementia of the Alzheimer type

Abstract: Family, twin and linkage studies in Alzheimer's disease are reviewed. Several of these studies appear to be burdened with sources of error, mainly related to sampling and clinical diagnoses. It was previously thought that early‐onset cases of Alzheimer's disease were heavily genetically influenced, whereas late‐onset cases were sporadic. The author questions whether this difference is mainly due to methodological error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 47 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Recurrence risk among siblings of those with AD (λ S ) have consistently ranged between four and five times higher than the risk to the general population (Hirst et al, 1994; Pericak-Vance et al, 1988; Sadovnick et al, 1989). Twin studies found higher concordance of AD among monozygotic twins (22-83%) than dizygotic twins (0-50%) (Bergem, 1994; Bergem et al, 1997; Breitner et al, 1993; Breitner et al, 1995), lending further support to genetic contributions to AD over only shared environmental contributors. Among early-onset families, patterns of AD inheritance have been consistent with classical Mendelian autosomal dominant inheritance, while the late-onset families have tended to suggest a multifactorial inheritance involving both genetic and non-genetic factors (Farrer et al, 1991; Rao et al, 1994; van Duijn et al, 1993).…”
Section: Alzheimer’s Disease: Characteristics Epidemiology and Genementioning
confidence: 91%
See 1 more Smart Citation
“…Recurrence risk among siblings of those with AD (λ S ) have consistently ranged between four and five times higher than the risk to the general population (Hirst et al, 1994; Pericak-Vance et al, 1988; Sadovnick et al, 1989). Twin studies found higher concordance of AD among monozygotic twins (22-83%) than dizygotic twins (0-50%) (Bergem, 1994; Bergem et al, 1997; Breitner et al, 1993; Breitner et al, 1995), lending further support to genetic contributions to AD over only shared environmental contributors. Among early-onset families, patterns of AD inheritance have been consistent with classical Mendelian autosomal dominant inheritance, while the late-onset families have tended to suggest a multifactorial inheritance involving both genetic and non-genetic factors (Farrer et al, 1991; Rao et al, 1994; van Duijn et al, 1993).…”
Section: Alzheimer’s Disease: Characteristics Epidemiology and Genementioning
confidence: 91%
“…While APOE is a critical contributor to genetic risk, more than a third of AD cases do not carry any APOE ε4 alleles, and as AD heritability has been estimated at ~80% (Bergem, 1994), this suggests much of the heritability has not yet been characterized. At most, APOE may account for 50% of the total genetic effect in AD (Farrer et al, 1997; Roses et al, 1995; Saunders et al, 1993).…”
Section: Genetics Of Alzheimer Disease: Late-onset Alzheimer Disease mentioning
confidence: 99%
“…Since heredity is reported to be a major risk factor for the development of AD, whereas environmental factors dominate in VaD (Bergem 1994), we have compared APOE alleles in blood samples from Norwegian twin pairs suffering from AD and VaD. In this population-based sample of 72 twin pairs, there were 38 AD and 22 VaD pairs. Among the AD twin pairs the probandwise concordance (both twins affected) rate was 83.2% in monozygotic (MZ) and 46.6% in dizygotic (DZ) pairs respectively, an observation which indicates that AD is heavily genetically determined.…”
mentioning
confidence: 99%
“…The most studied trigger of AD is genetic background. According to estimations, based on human pedigree analysis, up to 80% of all Alzheimer's cases are hereditary (Bergem, 1994). The first genes that were identified as genes in which mutations lead to fAD were: APP, BACE, and gamma-secretase genes, called PSEN1 and PSEN2.…”
Section: Hereditary Variance Of Amyloid Ptmsmentioning
confidence: 99%